Mecanismos de controle do arbítrio judicial e o livre convencimento : os critérios mínimos de fundamentação da decisão do Art. 315, § 2º, do código de processo penal - Fraga, Marcos Pippi (2022)
The following research seeks to study the article 315, § 2º, of the Criminal Procedure Code, which established minimum criteria for the justification of decisions, along the lines of the article 93, IX, of the Federal Constitution of 1988. The research is linked to the area of concentration Criminal System and Violence from Postgraduate Program in Criminal Sciences at PUCRS, emphasized on the research line Contemporary Legal-Criminal Systems. The main objective is to diagnose the applicability of the article 315, § 2º, of the Code of Criminal Procedure as a way to control judicial discretion. As specific objectives, work with the diagnosis on the state of the art of the duty to state reasons for criminal decisions, as well as the analysis of the psychological procedure of decision making and, finally, the critique of judicial discretion. Works with the hypothesis that the article 315, § 2º, of the Criminal Procedure Code has its effectiveness reduced by the maintenance of the article 155, which maintains the free of convictions and the almost unrestricted freedom of the magistrate. For this, the method employed is the hypothetical-deductive method, with a bibliographic and jurisprudential review technique. In the first chapter, proposes a brief contextualization of the duty to provide reasons for judicial decisions in the recent history of the Brazilian legal system, restricting the analysis to the modern period. From this perspective, seeks to assess the legislative provisions that, over the decades, have bound the magistrate to the need to state the reasons that underlie his decision. The second chapter aims at detailing each of the six hypotheses foreseen in article 315, § 2, of the Code of Criminal Procedure, which provide examples of causes that does not state the reasons for the decision. Seeks to understand the reasons that justify the need for defining the standards of reasoning, in opposition to the generic duty of article 93, IX, of the Federal Constitution. The third chapter justifies the premise adopted in this study: the insufficiency of these minimum criteria of reasoning in the face of the maintenance of article 155 of the Code of Criminal Procedure, which prescribe the magistrate's free persuasion, as this legal provision is inquisitorial in nature and protects an arbitrary zone of judicial decision that cannot be subject to judicial supervision. In conclusion is that the article 315, § 2º, of the Criminal Procedure Code will only be effective with the change of the judicial cultural paradigm and the total removal of the judicial discretion and other remaining circumstances of the inquisitorial criminal process.